Patella height following biplanar medial open-wedge high tibial osteotomy and its relevance for Clinical Outcome. Issue 3 (23rd March 2016) - Bode, Gerrit; Niemeyer, Philipp; Südkamp, Norbert P.; Feucht, Matthias; Mehl, Julian
Aims and Objectives: The medial medial open-wedge tibial osteotomy (OW HTO) has become increasingly important in the treatment of cartilage damage in the medial compartment with accompanying varus deformity in recent years. The technique of the biplanar, proximally initiated OW-HTO leads to a reduction of the patellar height. Relationships with functional outcome, and thus the clinical relevance of this observation, has not been investigated adequately so far. The aim of this study was to evaluate the influence of altered patellofemoral geometry on the functional outcome after OW HTO. Materials and Methods: In 205 patients (age 44.46 ± 10.43 years MW) with cartilage damage in the medial compartment and existing varus deformity biplanar, proximally directed OW HTO (TomoFix, Synthes, Solothurn, Switzerland) was perfermed between January 2005 and December 2013. Insall-Salvati index and Caton-Deschamps index were determined rom pre- and postoperative lateral radiographs of these patients. The evaluation of the patients was performed using standardized measuring instruments (preoperatively: visual analogue scale (VAS) and Lysholm score after surgery: VAS, Lysholm, KOOS and KOOS4). In the event of a radiological patella baja (Insall-Salvati index> 1.2; Caton-Dechamp less then 0, 6 correlation of patellar height and the functional scores was performed using SPSS 21.0 (IBM Corp., Armonk, United States). A p-value of 0.05 was considered statistically significant. Results: At an average follow-up of 68.65 (SD ± 30.26) months, a defect size of 4.32 MW (SD ± 3.01) cm2, a varus deformity of MW 6.04 (SD ± 2.83) ° and postoperative leg axis of MW 2.26 ± 1.74 ° valgus data analysis resulted in significant postoperative changes in the patellar indices (Insall-Salvati index preoperatively 0.94 ± 0.17 vs. 0.91 ± 0.20 postoperatively; Caton- Dechamp index preoperatively 1.03 ± 0.1, 69 vs. 0.89 ± 0.17 postoperatively, p = 0.00). The carried out correlation analysis revealed significant correlations for KOOS symptoms and KOOS4 (p = 0.034 and 0.01). Conclusion: The proximally directed biplanar medial open-wedge osteotomy leads to significant changes in the patellofemoral joint section in the sense of patella baja. These kinematic changes correlate with poorer postoperative functional results, so that in patients with preexisting pathological patellar height a modification of the classical osteotomy technique such as a to leave the tibial tuberosity attached tot he proximal tibia should be discussed.